(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: This study was conducted to develop a system of maternal death review in hospital of each level and in the community with a system of giving feedback and to take corrective action from the central level to periphery. Methods: It was a descriptive study with a cross sectional design. Study area were - 2 medical college hospitals, 4 district hospitals, 4 Upazilla hospitals and 12 unions. Study period was January 2007 to November 2007. The number of maternal death has occurred in that selected sites during the survey period was the sample size. Maternal death review committee has been formed at each hospital. In addition, OGSB Technical committee and National Technical committee had also been formed. To collect the information about the deceased in detail a structured pre-tested quetionairre has been used. In the community - community skilled birth attendants were assigned for collecting the data. In hospitals assigned persons were doctors working in Obstetrics & Gynaecology departments. Result: During the project period 101 maternal deaths were reported. One mother brought dead. So, she was excluded from the study. Among others, 97 forms were filled properly. Almost all (95%) mothers were housewife, 55% were primi gravida, 90% woman died within 3 hours of admission, 77% were critically ill during admission. PIH is the major killer (40%), next is haemorrhage (38%). Conclusion: Maternal death review provided information about the situation of care provided at hospitals of different level. This uncovered the causes of maternal deaths and identified the laps and gaps in the health care system. DOI: 10.3329/bjog.v24i1.6322 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) : 18-21